Minat Penggunaan E-Money di Masa Pandemi: Studi Kasus Mahasiswa Universitas Lampung - Erlina Rufaidah; Amar Ma'ruf; Pujiati Pujiati; Aryan Danil Mirza. BR (Jurnal Bisnis dan Manajemen (JBM), 2023)
The Covid-19 pandemic has encouraged massive use of e-money among the public. The lack of interaction between individuals during the pandemic has made e-money an increasingly necessary payment alternative. This research tries to analyze the driving factors behind the interest in using e-money during a pandemic. This study used a survey method on 97 respondents. The research results show evidence that interest in using e-money among students is influenced by perceptions regarding benefits, safety, and convenience. The government and related stakeholders need to increase the value of benefits, security and convenience to encourage the use of e-money among the wider community in the future